Need-for-touch and online purchase propensity: a comparative study of Portuguese and Chinese consumers - Duarte, Paulo (2020)
This study analyses the impact of Need-for-Touch (NFT) on online purchase propensity by evaluating the influence of the consumer's country of origin. Although NFT has been a major topic of research over the past years, the link between NFT and purchase propensity has rarely been empirically proven. For assessing the relationship an online questionnaire was made available in Portugal and China. A total of 295 complete responses were obtained and the data studied through exploratory and confirmatory factor analysis, namely multivariate analysis of variance and structural equation modeling using AMOS. The results indicate that the consumer's country of origin seems to affect the relevance of the sense of touch for apparel. Consumers with high levels of NFT are more likely to engage in additional brand touchpoints and consequently having stronger brand experiences. The impact of perceived information credibility and brand experience on the perceived product quality influences the propensity to search and to purchase online. Consumer NFT was shown having no direct influence on online purchase propensity but instead is mediated by other variables such as brand experience and the online research propensity. This study is innovative by comparing the NFT between two very different cultures and by providing insights on the relationships between cultural differences and NFT, which could be of great interest for Portuguese companies planning on investing in the Chinese market and vice versa.